Diagnosis and treatment of pediatric acquired aplastic anemia (AAA): An initial survey of the North American Pediatric Aplastic Anemia Consortium (NAPAAC). Issue 5 (27th November 2013) - Williams, David A.; Bennett, Carolyn; Bertuch, Alison; Bessler, Monica; Coates, Thomas; Corey, Seth; Dror, Yigal; Huang, James; Lipton, Jeffrey; Olson, Timothy S.; Reiss, Ulrike M.; Rogers, Zora R.; et al.
<x xml:space="preserve">Abstract</x> Background Randomized clinical trials in pediatric aplastic anemia (AA) are rare and data to guide standards of care are scarce. Procedure Eighteen pediatric institutions formed the North American Pediatric Aplastic Anemia Consortium to foster collaborative studies in AA. The initial goal of NAPAAC was to survey the diagnostic studies and therapies utilized in AA. Results Our survey indicates considerable variability among institutions in the diagnosis and treatment of AA. There were areas of general consensus, including the need for a bone marrow evaluation, cytogenetic and specific fluorescent in situ hybridization assays to establish diagnosis and exclude genetic etiologies with many institutions requiring results prior to initiation of immunosuppressive therapy (IST); uniform referral for hematopoietic stem cell transplantation as first line therapy if an HLA‐identical sibling is identified; the use of first‐line IST containing horse anti‐thymocyte globulin and cyclosporine A (CSA) if an HLA‐identical sibling donor is not identified; supportive care measures; and slow taper of CSA after response. Areas of controversy included the need for telomere length results prior to IST, the time after IST initiation defining a treatment failure; use of hematopoietic growth factors; the preferred rescue therapy after failure of IST; the use of specific hemoglobin and platelet levels as triggers for transfusion support; the use of prophylactic antibiotics; and follow‐up monitoring after completion of treatment. Conclusions These initial survey results reflect heterogeneity in diagnosis and care amongst pediatric centers and emphasize the need to develop evidence‐based diagnosis and treatment approaches in this rare disease. Pediatr Blood Cancer 2014;61:869–874. © 2013 Wiley Periodicals, Inc.